1989
DOI: 10.1002/mrd.1080010407
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus of the boar spermatozoon: Structure and modifications in frozen, frozen‐thawed, or sodium dodecyl sulfate‐treated cells

Abstract: After cryosubstitution and Epon embedding, or after Nanoplast embedding and very thin sectioning, the chromatin of ejaculated or diluted boar spermatozoa appears to be formed of DNA fibers embedded in a quite homogeneous matrix. After sodium dodecyl sulfate (SDS) treatment, and to a lesser extent after freeze-thawing, the DNA fibers are present mostly between cords, probably proteinaceous in nature. The quantity of free sulfhydryl (SH) groups, as calculated from staining by DACM and flow fluorometry, is increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…They reported that the proportions of spermatozoa with fragmented DNA increased from 4.80% in fresh semen to 8.90% after freezing and thawing of bull semen. The destabilizing effect of cryopreservation on sperm chromatin may stem from the high ionic strength in frozen nuclei (Courtens et al 1989) and excessive intracellular influx of free calcium ions (Zhao & Buhr 1995) leading to activation of nucleoprotein-degrading enzymes such as acrosin (Zirkin et al 1980), endonucleases (Krzyzosiak et al 2000) and phospholipases with their toxic metabolites, lysolecithins (Upreti et al 1999). Evenson (1999) suggested that loss of DNA integrity ≥ 20% might announce lower fertility.…”
Section: Dna Integritymentioning
confidence: 99%
“…They reported that the proportions of spermatozoa with fragmented DNA increased from 4.80% in fresh semen to 8.90% after freezing and thawing of bull semen. The destabilizing effect of cryopreservation on sperm chromatin may stem from the high ionic strength in frozen nuclei (Courtens et al 1989) and excessive intracellular influx of free calcium ions (Zhao & Buhr 1995) leading to activation of nucleoprotein-degrading enzymes such as acrosin (Zirkin et al 1980), endonucleases (Krzyzosiak et al 2000) and phospholipases with their toxic metabolites, lysolecithins (Upreti et al 1999). Evenson (1999) suggested that loss of DNA integrity ≥ 20% might announce lower fertility.…”
Section: Dna Integritymentioning
confidence: 99%
“…It is worth noting that, in the literature, there are still inconsistent reports regarding the relationship between sperm chromatin structure and cryopreservation-induced DNA modification (16,17). Most of the earlier reports evaluated the basic association between DNA integrity and cryopreservation either in animal models or in human sperm but did not address the amount of sperm DNA damage that can tolerate the process of cryopreservation (18)(19)(20). Our recent study using the sperm from a different cohort of patients with male factor infertility demonstrated an increased chromatin modification in patients with teratospermia suggesting that sperm with abnormal morphology has a higher risk of undergoing chromatin modification by cryopreservation (5).…”
Section: Figurementioning
confidence: 92%
“…Sperm susceptibility to nuclear chromatin decondensation (NCD) was tested according to methods of Bedford et al. (1973) and Courtens et al. (1989) with some modifications.…”
Section: Methodsmentioning
confidence: 99%